Vitamin D Deficiency Associated With Markers of Cardiovascular Disease in Children With Obesity - Marisa Censani MD; Hoda T. Hammad MS, MPH; Paul J. Christos DrPH, MS; Tiffany Schumaker DO (SAGE Publishing, 2018)
Adult studies have reported associations of low 25-hydroxyvitamin D (25OHD) with dyslipidemia and cardiovascular disease; however, there are scarce pediatric data regarding relationships between vitamin D status and specific lipid markers affecting cardiovascular risk. In this cross-sectional study of children evaluated at university-based pediatric endocrinology clinics, 178 patients meeting criteria for overweight or obesity had 25OHD levels assessed over a 2-year period; 60 of 178 had non-HDL (high-density lipoprotein) cholesterol and fasting lipid parameters performed. Patients with 25OHD <20 ng/mL had significantly higher non-HDL cholesterol (134.76 ± 47.32 vs 108.85 ± 31.14, P < .03), triglyceride (TG)/HDL ratio (3.09 ± 2.26 vs 1.82 ± 1.18, P = .03), total cholesterol (TC)/HDL ratio (4.23 ± 1.23 vs 3.40 ± 1.05, P < .01), TC (184.15 ± 40.19 vs 158.89 ± 30.10, P < .01), and TG (134.76 ± 47.32 vs 78.93 ± 37.46, P < .03) compared with 25OHD ≥20 ng/mL. Vitamin D deficiency was significantly associated with increase in atherogenic lipids and markers of early cardiovascular disease. These findings suggest that vitamin D deficiency may have negative effects on lipid parameters with increase in cardiovascular risk.